2016
DOI: 10.1002/bies.201600121
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of X chromosome inactivation and epigenomic features of the inactive X depend on cellular contexts

Abstract: Establishment of X chromosome inactivation and epigenomic features of the inactive X depend on cellular contexts C eline Vallot, Jean-François Ouimette and Claire Rougeulle à X chromosome inactivation (XCI) is an essential epigenetic process that ensures X-linked gene dosage equilibrium between sexes in mammals. XCI is dynamically regulated during development in a manner that is intimately linked to differentiation. Numerous studies, which we review here, have explored the dynamics of X inactivation and reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 119 publications
(157 reference statements)
1
35
0
Order By: Relevance
“…Nanog, Oct4, and Sox2 mark the naïve state and collectively repress the ubiquitin ligase Rnf12 (21) that lies in the Xist TAD (17), prior to dosage compensation. As naïve state TFs become depleted, Rnf12 is activated and marks Rex1 for degradation (21). Rex1 is another naïve TF that, along with KLF4 and c-Myc, activates the lncRNA Tsix (21).…”
Section: Dosage Compensation In the Mousementioning
confidence: 99%
See 2 more Smart Citations
“…Nanog, Oct4, and Sox2 mark the naïve state and collectively repress the ubiquitin ligase Rnf12 (21) that lies in the Xist TAD (17), prior to dosage compensation. As naïve state TFs become depleted, Rnf12 is activated and marks Rex1 for degradation (21). Rex1 is another naïve TF that, along with KLF4 and c-Myc, activates the lncRNA Tsix (21).…”
Section: Dosage Compensation In the Mousementioning
confidence: 99%
“…As naïve state TFs become depleted, Rnf12 is activated and marks Rex1 for degradation (21). Rex1 is another naïve TF that, along with KLF4 and c-Myc, activates the lncRNA Tsix (21). Tsix is the key repressor of Xist function in mice and negatively regulates Xist expression in cis (17).…”
Section: Dosage Compensation In the Mousementioning
confidence: 99%
See 1 more Smart Citation
“…20 Variations in Xi frequency have been reported with age, pregnancy, the use of oral contraceptives, fluctuations in menstrual cycle and neoplasia. [21][22][23][24][25] Moore et al found that the frequency of the sex chromatin in the nuclei of female hosts was low in malignant tissues, appearing in only about one-third of tumours in comparison to non-malignant tissues; this finding was attributed to the diverse chromosomal abnormalities that occur in malignancy.…”
Section: Distinct X Chromosome Perturbations In Malignancymentioning
confidence: 99%
“…34,35 The misexpression of XIST may potentially be a mechanism underlying oncogenesis and low XIST levels may reduce X inactivation with continuous X reactivation. 20 However, the molecular cascade that alters X inactivation and X chromosome copy numbers in both female and male cancer cells remains undetermined.…”
mentioning
confidence: 99%